Antibacterial PP fan shell material and preparation method thereof

By adopting a multi-component synergistic enhancement method in PP fan shell materials, the synergistic effects of modified lignin and nanomodified montmorillonite are used to solve the problem of insufficient antibacterial, mechanical and thermal stability of PP materials, and efficient antibacterial, mechanical and thermal performance improvements are achieved.

CN119613866AInactive Publication Date: 2025-03-14HUIZHOU FREED IND CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411637308.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-03-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing PP fan shell materials are prone to breed bacteria, have insufficient mechanical properties and poor heat resistance, and inorganic antibacterial agents are prone to agglomeration in the PP matrix, have uneven antibacterial properties, and are difficult to control the release rate, which affects the product service life and user experience.

Method used

A multi-component system consisting of polypropylene compound, polyethylene glycol grafted maleic anhydride, modified lignin, nanomodified montmorillonite, silver nitrate, coupling agent KH550, calcium stearate and antioxidant is adopted to improve the reactivity and dispersion of lignin through thiolation and carboxylation modification, and the compatibility and interface binding force of montmorillonite are improved through three-step modification to achieve synergistic effect.

Benefits of technology

It significantly improves the tensile strength, toughness and thermal stability of the material, achieves the durability of antibacterial properties, and maintains an antibacterial efficiency of more than 95% after 7 days, improving the overall performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005137434320000161
    Figure BDA0005137434320000161
  • Figure BDA0005137434320000171
    Figure BDA0005137434320000171
  • Figure BDA0005137434320000172
    Figure BDA0005137434320000172
Patent Text Reader

Abstract

The invention relates to the technical field of fan shell materials, in particular to an antibacterial PP (polypropylene) fan shell material and a preparation method thereof. The polypropylene composite material is prepared from the following components in parts by weight: 80 to 90 parts of polypropylene composite material, 1 to 3 parts of polyethylene glycol grafted maleic anhydride, 1 to 5 parts of modified lignin, 8 to 15 parts of nano modified montmorillonite, 1 to 4 parts of silver nitrate, 1 to 3 parts of coupling agent KH550, 0.1 to 0.5 part of calcium stearate and 0.3 to 0.6 part of antioxidant, through double modification of lignin and three-step modification of montmorillonite, the dispersity and interface bonding strength of the filler are remarkably improved, the tensile strength of the material is improved by 37% or above, and meanwhile good toughness is kept; a multi-component synergistic system realizes the persistence of the antibacterial performance, and the antibacterial efficiency of 95% or above is still kept after 7 days. Thirdly, through the synergistic effect of the modified lignin and the nano-montmorillonite, the thermal stability of the material is remarkably improved, and the initial degradation temperature is increased by 20-35 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fan casing materials, and in particular to an antibacterial PP fan casing material and a preparation method thereof. Background Art

[0002] Polypropylene (PP) is widely used in home appliances such as fan housings due to its excellent mechanical properties, good processing performance and low cost. However, in actual use, PP fan housings are prone to bacteria growth, and have problems such as insufficient mechanical properties and poor heat resistance, which seriously affect the product's service life and user experience.

[0003] At present, the main method to improve the antibacterial properties of PP materials is to add inorganic antibacterial agents, such as nanosilver, zinc oxide, etc. Although these methods can achieve a certain antibacterial effect, there are the following prominent problems: first, inorganic antibacterial agents are easy to agglomerate in the PP matrix, resulting in uneven antibacterial properties; second, the release rate of antibacterial agents is difficult to control, and it is impossible to achieve long-term antibacterial properties; third, the single addition of inorganic antibacterial agents often reduces the mechanical properties of the material. At the same time, the prior art also attempts to modify PP using lignin or montmorillonite, but due to the poor compatibility of these fillers with the PP matrix, it is difficult to achieve an ideal enhancement effect in practical applications. Summary of the invention

[0004] In view of the above problems, the present invention provides an antibacterial PP fan casing material and a preparation method thereof.

[0005] The object of the present invention is to provide an antibacterial PP fan housing material, which is composed of the following components in parts by weight:

[0006] 80-90 parts of polypropylene compound, 1-3 parts of polyethylene glycol grafted maleic anhydride, 1-5 parts of modified lignin, 8-15 parts of nano-modified montmorillonite, 1-4 parts of silver nitrate, 1-3 parts of coupling agent KH550, 0.1-0.5 parts of calcium stearate, and 0.3-0.6 parts of antioxidant;

[0007] Wherein, the polypropylene compound is prepared by mixing homopolymer PP and random copolymer PP in a mass ratio of 1:1.5;

[0008] The homopolymer PP has a melt index of 2.0-3.0 g / 10 min at 230°C / 2.16 kg and a density of 0.90-0.92 g / cm 3 , isotacticity is 96-98%;

[0009] The random copolymer PP has an ethylene content of 3-5wt%, a melt index of 230°C / 2.16k of 4.0-5.0g / 10min, and a density of 0.89-0.90g / cm 3 .

[0010] Preferably, the polyethylene glycol molecular weight of the polyethylene glycol grafted maleic anhydride is 2000-4000, the maleic anhydride grafting rate is 0.8-1.2%, and the melt index 190°C / 2.16kg is 5-8g / 10min.

[0011] Preferably, the antioxidant is a mixture of type 1010 antioxidant and type 168 antioxidant in a mass ratio of 1:1.

[0012] Preferably, the modified lignin is prepared by the following steps:

[0013] (1) adding nano-lignin and 1-ethyl-3-methylimidazolium hydrogen sulfate in a mass ratio of 100:20-30 into a reaction kettle, and dispersing them at a temperature of 65±4° C. for 1-3 hours under the action of a disperser with a power of 30-60 kW to obtain a dispersion;

[0014] (2) adding 15-25 wt% of 3-mercaptopropionic acid to the dispersion in step (1), reacting at 65±4° C. for 6-10 h under 0.1 MPa nitrogen protection, and filtering, washing with water, and drying to obtain thiolated lignin;

[0015] (3) The thiolated lignin described in step (2), 30% hydrogen peroxide, and sodium periodate are mixed in a weight ratio of 10-15:5-8:5-8, reacted at a temperature of 70±10° C. and a rotation speed of 60±10 r / min for 8±2 h, filtered, washed with water until neutral, dried at 60±5° C. for 4±1 h, and crushed through a 200-mesh sieve to obtain the modified lignin.

[0016] Preferably, the nano-lignin is prepared by the following steps:

[0017] (1) stirring poplar wood kraft lignin and a sodium hydroxide solution with a mass concentration of 5-10 wt% at 52±3°C and a rotation speed of 400±200 rpm for 30±10 min, and filtering to obtain alkalized lignin;

[0018] (2) adding a tetrabutylammonium bromide solution having a concentration of 0.0875±0.0375wt%, a mixed solution of 30% hydrogen peroxide and deionized water in a mass ratio of 32.5±7.5:750±250, and 0.5-1.0wt% lignin peroxidase to the alkalized lignin in step (1), and reacting at 52±3°C and a rotation speed of 600±50rpm for 1.5±0.5h;

[0019] (3) The reaction solution of step (2) was filtered, and the precipitate was washed with clean water 3 times and anhydrous ethanol 2 times, dried at 50±5° C. for 2±1 h, and then crushed at 50±5° C. and 950±50 rpm for 9±1 h to obtain the nano-lignin.

[0020] Preferably, the nano-modified montmorillonite is prepared by the following steps:

[0021] (1) Na+ montmorillonite, deionized water, and hexadecyltrimethylammonium bromide were mixed in a mass ratio of 1-10:1-5:1, stirred at 140±20°C for 9±3h, centrifuged at 10500±500r / min for 15±5min, washed with deionized water 3 times, washed with anhydrous ethanol 3 times, and dried at 60±5°C for 3±1h to obtain intercalated modified montmorillonite;

[0022] (2) mixing the intercalated modified montmorillonite described in step (1) with deionized water in a mass ratio of 1-10:20±10, heating to 115±5° C., ultrasonically treating for 30±10 min, and adding a polyethylene glycol solution with a concentration of 22.5±2.5% and a molecular weight of 4000±500;

[0023] (3) treating the mixture obtained in step (2) in a six-tube microwave plasma modification device under the conditions of a working power supply of 300±100V, a microwave power of 300±100W, and an oxygen flow rate of 50±10mL / min for 4.5±1.5h to obtain the nano-modified montmorillonite.

[0024] The method for preparing the antibacterial PP fan casing material comprises the following steps:

[0025] The components are put into a twin-screw extruder and extruded into granules, wherein:

[0026] The screw diameter is 30 mm and the aspect ratio is 40:1;

[0027] The temperature of the feeding section is 165±5℃, the temperature of the compression section is 175±5℃, the temperature of the melting section is 185±5℃, the temperature of the homogenization section is 195±5℃, and the temperature of the metering section is 185±5℃;

[0028] The screw speed is 100±20rpm, the main motor current is 80±10A, the vacuum degree is -0.08MPa, and the feeding rate is 15±5kg / h.

[0029] Preferably, the order of adding the components is: first adding the polypropylene compound and polyethylene glycol grafted maleic anhydride, and then adding the modified lignin, nano-modified montmorillonite, silver nitrate, coupling agent KH550, calcium stearate and antioxidant in sequence.

[0030] Preferably, the screw assembly of the twin-screw extruder consists of a feeding section, a compression section, a melting section, a homogenizing section and a metering section, and the screw elements are arranged in sequence along the length direction of the barrel.

[0031] Preferably, a reverse stirring element is arranged in the feeding section, and kneading blocks are arranged in the melting section and the homogenizing section, respectively.

[0032] First, the reactivity and dispersibility of lignin are significantly improved through dual modification of thiol and carboxyl. The introduction of thiol can not only physically entangle with the PP molecular chain through free radical transfer, but also give full play to the antioxidant properties of lignin. The introduction of carboxyl enhances the interfacial bonding between lignin and other components, forming a stable network structure.

[0033] Secondly, the present invention designs an innovative three-step modification process, which achieves deep modification of montmorillonite through quaternary ammonium salt intercalation, ultrasonic exfoliation and plasma treatment. The polar group network constructed on the surface of montmorillonite by plasma treatment not only improves its compatibility with the PP matrix, but also produces a synergistic effect with the modified lignin, jointly improving the comprehensive performance of the composite material.

[0034] More importantly, the present invention achieves a synergistic effect among lignin, montmorillonite and silver nitrate by precisely controlling the ratio of each component and the modification process. The labyrinth structure formed by nano-modified montmorillonite can effectively regulate the release rate of silver ions, while the antioxidant properties of the modified lignin prevent the oxidation and inactivation of silver nanoparticles. The synergistic effect of the two significantly prolongs the antibacterial duration of the material. At the same time, this multi-component system also constructs a unique three-dimensional network structure, which greatly improves the mechanical properties and thermal stability of the material.

[0035] The present invention has the following outstanding technical effects: First, through the double modification of lignin and the three-step modification of montmorillonite, the dispersibility and interfacial bonding strength of the filler are significantly improved, and the tensile strength of the material is increased by more than 37%, while maintaining good toughness. Secondly, the innovative multi-component synergistic system realizes the persistence of antibacterial properties, and the antibacterial efficiency remains above 95% after 7 days. Thirdly, the synergistic effect of modified lignin and nano-montmorillonite significantly improves the thermal stability of the material, and the initial degradation temperature is increased by 20-35°C. In addition, the preparation process of the present invention is simple and controllable, the raw material source is wide, and it has good prospects for industrial application.

[0036] The realization of these technical effects stems from the innovation of the present invention at the molecular design level: by introducing thiol and carboxyl groups on the lignin molecules, multiple forces with the PP molecular chain are formed; the polar group network on the surface of montmorillonite provides a stable interface binding site; the synergistic effect between these molecules jointly constructs an efficient mechanical enhancement and antibacterial controlled release system. At the same time, the synergistic network formed between the components also significantly improves the crystallization behavior of the material, increases the crystallinity, and shortens the crystallization time, which is of great significance to improving the production efficiency of the material.

[0037] In general, the present invention successfully solves the technical problems of PP fan casing materials in terms of antibacterial properties, mechanical properties and thermal stability through the innovative design of multi-component synergistic enhancement, and provides a new technical path for related fields. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0039] Example 1

[0040] This embodiment provides an antibacterial PP fan housing material and a preparation method thereof. The material has excellent antibacterial properties, good mechanical properties and processing properties, and the preparation method thereof is as follows:

[0041] 1. Preparation of modified lignin

[0042] First, the preparation of nano lignin is carried out:

[0043] (1) Take 10 kg of poplar kraft lignin with a purity of 98%, mix it with a sodium hydroxide solution with a concentration of 5 wt% (1 part of sodium hydroxide, 500 parts of deionized water), and stir it at 52° C. and 400 rpm for 30 minutes. In this step, the mild alkaline conditions can effectively activate the hydroxyl groups in the lignin molecules and improve their reactivity. Then, filter under a vacuum degree of -0.08 MPa to obtain alkalized lignin.

[0044] (2) Tetrabutylammonium bromide aqueous solution (0.2 parts of tetrabutylammonium bromide and 500 parts of deionized water are prepared into a solution with a concentration of 0.05wt%) is added to the alkalized lignin in sequence, wherein tetrabutylammonium bromide as a phase transfer catalyst can significantly improve the efficiency of the subsequent modification reaction. Then a mixture of 30% hydrogen peroxide and deionized water (prepared at a mass ratio of 25:500) is added, and finally a lignin peroxidase with an activity of 50U / mg (accounting for 0.5wt% of the lignin mass) is added. The reaction is carried out at 52°C and a rotation speed of 600rpm for 1h, and the controllable degradation and nano-crystallization of lignin are achieved under the action of the enzyme.

[0045] (3) The reaction solution was filtered, and the resulting precipitate was washed three times with clean water and twice with anhydrous ethanol (purity 99.5%) to fully remove the residual reagents. The washed product was dried at 50°C for 2 hours to ensure that the water was fully removed. Then, it was crushed at 950 rpm for 9 hours at the same temperature to obtain nano-lignin with a particle size of about 200 nm. This nano-scale lignin has a larger specific surface area, which is conducive to the subsequent modification reaction.

[0046] Then carry out thiol modification:

[0047] (4) The prepared nano-lignin was mixed with 1-ethyl-3-methylimidazolium hydrogen sulfate with a purity of 99% at a mass ratio of 100:20 and put into a reactor. The mixture was dispersed at 65° C. for 1 h under the action of a 30 kW power disperser. The use of ionic liquid in this step can significantly improve the dispersibility of lignin and create favorable conditions for the subsequent thiol reaction.

[0048] (5) Add 3-mercaptopropionic acid (mass fraction 15 wt%) with a purity of 98% to the dispersion, and react at 65° C. for 6 h under 0.1 MPa nitrogen protection. Nitrogen protection can effectively prevent the oxidation of the mercapto group and improve the modification efficiency. After the reaction, the mixture is filtered, washed with water, and dried to obtain mercaptolated lignin.

[0049] Finally, carboxyl modification is performed:

[0050] (6) The thiolated lignin, 30% hydrogen peroxide, and sodium periodate were mixed in a weight ratio of 10:5:5 and reacted at 70°C and 60 r / min for 8 hours. This step introduces carboxyl groups into the lignin molecules through oxidation reaction to improve its compatibility with the matrix. After the reaction, the mixture was filtered, washed with water until neutral, dried at 60°C for 4 hours, and finally crushed through a 200-mesh sieve to obtain modified lignin.

[0051] 2. Preparation of Nano-modified Montmorillonite

[0052] (1) Na+ montmorillonite, deionized water, and hexadecyltrimethylammonium bromide were fully mixed in a mass ratio of 1:1:1, and stirred at 140°C for 9 hours. In this step, the quaternary ammonium salt can effectively intercalate and modify the montmorillonite to increase the interlayer spacing. Subsequently, the mixture was centrifuged at a speed of 10500 r / min for 15 minutes, washed with deionized water and anhydrous ethanol three times each, and dried at 60°C for 3 hours to obtain intercalated modified montmorillonite.

[0053] (2) The intercalated modified montmorillonite and deionized water are mixed in a mass ratio of 1:20, heated to 115° C., and subjected to ultrasonic treatment at a power of 600 W for 30 min. This step can further peel off the montmorillonite layer. Subsequently, a polyethylene glycol solution with a concentration of 22.5% and a molecular weight of 4000 is added. The addition of polyethylene glycol can improve the compatibility of montmorillonite with the matrix.

[0054] (3) The obtained mixture was placed in a six-tube microwave plasma modification device and treated for 4.5 hours under the conditions of a working power supply of 300 V, a microwave power of 300 W, and an oxygen flow rate of 50 mL / min. Plasma treatment can introduce polar groups on the surface of montmorillonite, further improving its interface bonding with the matrix.

[0055] 3. Preparation of antibacterial PP fan casing material

[0056] Mix the following components: 80 parts of polypropylene compound (melt index 2.0g / 10min, density 0.90g / cm 3 , homopolymer PP with isotacticity of 96% and ethylene content of 3wt%, melt index of 4.0g / 10min, density of 0.89g / cm 3 Random copolymer PP is compounded in a mass ratio of 1:1.5), 1 part of polyethylene glycol grafted maleic anhydride (polyethylene glycol molecular weight 2000, maleic anhydride grafting rate 0.8%), 1 part of the modified lignin prepared above, 8 parts of nano-modified montmorillonite, 1 part of silver nitrate with a purity of 99.9%, 1 part of coupling agent KH550, 0.1 part of calcium stearate, and 0.3 part of antioxidant (1010 type and 168 type are mixed in a mass ratio of 1:1).

[0057] The above components are sequentially put into a twin-screw extruder (screw diameter 30mm, aspect ratio 40:1), wherein the screw assembly consists of a feed section, a compression section, a melting section, a homogenization section and a metering section, and a reverse stirring element is set in the feed section, and kneading blocks are set in the melting section and the homogenization section respectively to enhance the mixing effect. The specific process parameters are: feed section temperature 165℃, compression section temperature 175℃, melting section temperature 185℃, homogenization section temperature 195℃, metering section temperature 185℃, screw speed 100rpm, main engine motor current 80A, vacuum degree -0.08MPa, feeding rate 15kg / h. This temperature program design ensures that each component is fully melted and mixed while avoiding material degradation.

[0058] Example 2

[0059] This embodiment provides a PP fan housing material with high antibacterial properties and a preparation method thereof. The method makes full use of the antioxidant properties of modified lignin and the barrier properties of nano-montmorillonite, and the specific steps are as follows:

[0060] 1. Preparation of modified lignin

[0061] First, the preparation of nano lignin is carried out:

[0062] (1) Take 12 kg of poplar wood kraft lignin with a purity of 98%, prepare a sodium hydroxide solution with a concentration of 8 wt% (2 parts of sodium hydroxide, 750 parts of deionized water), and stir for 35 minutes at 55°C and 300 rpm. The selection of this temperature and speed can ensure that the lignin is fully swollen without degradation. After vacuum filtration at -0.08 MPa, alkalized lignin is obtained.

[0063] (2) Tetrabutylammonium bromide aqueous solution (0.4 parts of tetrabutylammonium bromide, 750 parts of deionized water, concentration 0.0875wt%) was added to the alkalized lignin in sequence, followed by a mixture of 30% hydrogen peroxide and deionized water (mass ratio 32.5:750), and finally a lignin peroxidase with an activity of 55U / mg (accounting for 0.8wt% of the lignin mass). The reaction was carried out at 54°C and a rotation speed of 625rpm for 1.5h to achieve directional degradation of lignin under mild conditions.

[0064] (3) The reaction solution was filtered, and the precipitate was washed with water three times and anhydrous ethanol (purity 99.7%) twice, dried at 52°C for 2.5 hours, and then crushed at 975 rpm for 9.5 hours at the same temperature to obtain nano-lignin with a particle size of about 250 nm. Precisely controlled crushing conditions are conducive to obtaining a uniform particle size distribution.

[0065] Then carry out thiol modification:

[0066] (4) The nano-lignin was mixed with 1-ethyl-3-methylimidazolium hydrogen sulfate with a purity of 99.5% in a mass ratio of 100:25, put into a reactor, and dispersed at 67° C. for 2 h under the action of a 45 kW power disperser to give full play to the dispersing effect of the ionic liquid.

[0067] (5) Add 3-mercaptopropionic acid (mass fraction 20 wt%) with a purity of 99% to the dispersion, and react at 67°C for 8 h under the protection of 0.1 MPa nitrogen. Prolonging the reaction time in this step can increase the degree of thiolation. After suction filtration, water washing and drying, thiolated lignin is obtained.

[0068] Finally, carboxyl modification is performed:

[0069] (6) The thiolated lignin, 30% hydrogen peroxide, and sodium periodate were mixed in a weight ratio of 12:6:6, and reacted at 75°C and a speed of 65 r / min for 9 hours. A higher reaction temperature can accelerate the carboxylation reaction rate. The mixture was filtered, washed with water until neutral, dried at 62°C for 4.5 hours, and crushed through a 200-mesh sieve to obtain modified lignin.

[0070] 2. Preparation of Nano-modified Montmorillonite

[0071] (1) Na+ montmorillonite, deionized water, and hexadecyltrimethylammonium bromide were mixed in a mass ratio of 5:3:1 and stirred at 150°C for 10 hours. This condition can achieve sufficient interlayer intercalation. Centrifuge at 11000 r / min for 18 minutes, wash with deionized water and anhydrous ethanol three times each, and dry at 62°C for 3.5 hours to obtain intercalated modified montmorillonite.

[0072] (2) The intercalated modified montmorillonite and deionized water were mixed in a mass ratio of 5:25, heated to 118° C., and ultrasonically treated for 35 min at a power of 625 W, followed by adding a polyethylene glycol solution with a concentration of 24% and a molecular weight of 4250. Increasing the ultrasonic power in this step can improve the stripping effect.

[0073] (3) The mixture was treated in a six-tube microwave plasma modification device under the conditions of a working power supply of 350 V, a microwave power of 350 W, and an oxygen flow rate of 55 mL / min for 5 h. This condition can form more polar groups on the surface of montmorillonite.

[0074] 3. Preparation of antibacterial PP fan casing material

[0075] Mix the following components: 85 parts of polypropylene compound (melt index 2.5g / 10min, density 0.91g / cm 3 , homopolymer PP with isotacticity of 97% and ethylene content of 4wt%, melt index of 4.5g / 10min, density of 0.895g / cm 3 Random copolymer PP is compounded in a mass ratio of 1:1.5), 2 parts of polyethylene glycol grafted maleic anhydride (polyethylene glycol molecular weight 3000, maleic anhydride grafting rate 1.0%), 3 parts of modified lignin, 11.5 parts of nano-modified montmorillonite, 2.5 parts of silver nitrate, 2 parts of coupling agent KH550, 0.3 parts of calcium stearate, and 0.45 parts of antioxidant.

[0076] A twin-screw extruder (screw diameter 30mm, aspect ratio 40:1) was used for processing, and the temperature program was: 170℃ for the feeding section, 180℃ for the compression section, 190℃ for the melting section, 200℃ for the homogenization section, and 190℃ for the metering section. The screw speed was set to 110rpm, the main motor current to 85A, the vacuum degree to -0.08MPa, and the feeding rate to 18kg / h. Shearing elements were added to the feeding section and the melting section to improve the mixing effect.

[0077] Example 3

[0078] This embodiment provides a high-performance antibacterial PP fan housing material and a preparation method thereof. The method achieves excellent compatibility of lignin, montmorillonite and the matrix by optimizing modification conditions and process parameters. The specific steps are as follows:

[0079] 1. Preparation of modified lignin

[0080] First, the preparation of nano lignin is carried out:

[0081] (1) Take 15 kg of 99% pure poplar kraft lignin, prepare a 10 wt% sodium hydroxide solution (3 parts of sodium hydroxide, 1000 parts of deionized water), and stir at 58°C and 500 rpm for 40 minutes. A higher concentration of alkali solution can accelerate the activation process of lignin. After vacuum filtration at -0.08 MPa, alkalized lignin is obtained.

[0082] (2) Tetrabutylammonium bromide aqueous solution (0.6 parts of tetrabutylammonium bromide, 1000 parts of deionized water, concentration 0.125wt%) was added to the alkalized lignin in sequence, followed by a mixture of 30% hydrogen peroxide and deionized water (mass ratio 40:1000), and finally a lignin peroxidase with an activity of 60U / mg (accounting for 1.0wt% of the lignin mass). The reaction was carried out at 55°C and a rotation speed of 650rpm for 2h to achieve deep nano-crystallization of lignin.

[0083] (3) The reaction solution was filtered, and the precipitate was washed with water three times and anhydrous ethanol (purity 99.9%) twice, dried at 54°C for 3 hours, and then crushed at 1000 rpm for 10 hours at the same temperature to obtain nano-lignin with a particle size of about 300 nm. A longer crushing time ensures a more uniform particle size distribution of the product.

[0084] Then carry out thiol modification:

[0085] (4) The nano-lignin was mixed with 1-ethyl-3-methylimidazole hydrogen sulfate with a purity of 99.8% in a mass ratio of 100:30, put into a reactor, and dispersed at 69° C. for 3 h under the action of a 60 kW power disperser to achieve a sufficient dispersion effect.

[0086] (5) Add 3-mercaptopropionic acid (mass fraction 25 wt%) with a purity of 99.5% to the dispersion, and react at 69° C. for 10 h under the protection of 0.1 MPa nitrogen. Higher reaction temperature and longer reaction time can increase the grafting rate of mercapto groups. After filtration, water washing and drying, mercaptolated lignin is obtained.

[0087] Finally, carboxyl modification is performed:

[0088] (6) The thiolated lignin, 30% hydrogen peroxide, and sodium periodate were mixed in a weight ratio of 15:8:8, and reacted at 80°C and a rotation speed of 70 r / min for 10 hours. This step achieves high-density carboxylation of the lignin surface by optimizing the reaction conditions. After the reaction, the mixture was filtered, washed with water until neutral, dried at 65°C for 5 hours, and crushed through a 200-mesh sieve to obtain modified lignin.

[0089] 2. Preparation of Nano-modified Montmorillonite

[0090] (1) Na+ montmorillonite, deionized water, and hexadecyltrimethylammonium bromide were mixed in a mass ratio of 10:5:1 and stirred at 160°C for 12 hours. High temperature and long-term treatment can achieve complete intercalation of montmorillonite. Centrifuge at 11000 r / min for 20 minutes, wash with deionized water and anhydrous ethanol 4 times each, and dry at 65°C for 4 hours to obtain intercalated modified montmorillonite.

[0091] (2) The intercalated modified montmorillonite and deionized water were mixed in a mass ratio of 10:30, heated to 120°C, and subjected to ultrasonic treatment at a power of 650W for 40 minutes, followed by the addition of a polyethylene glycol solution with a concentration of 25% and a molecular weight of 4500. The strong ultrasonic treatment in this step can promote the complete exfoliation of the montmorillonite.

[0092] (3) The mixture was treated in a six-tube microwave plasma modification device under the conditions of a working power supply of 400 V, a microwave power of 400 W, and an oxygen flow rate of 60 mL / min for 6 h to achieve deep modification of the montmorillonite surface.

[0093] 3. Preparation of antibacterial PP fan casing material

[0094] Mix the following components: 90 parts of polypropylene compound (melt index 3.0g / 10min, density 0.92g / cm 3 , homopolymer PP with isotacticity of 98% and ethylene content of 5wt%, melt index of 5.0g / 10min, density of 0.90g / cm 3 Random copolymer PP is compounded in a mass ratio of 1:1.5), 3 parts of polyethylene glycol grafted maleic anhydride (polyethylene glycol molecular weight 4000, maleic anhydride grafting rate 1.2%), 5 parts of modified lignin, 15 parts of nano-modified montmorillonite, 4 parts of silver nitrate, 3 parts of coupling agent KH550, 0.5 parts of calcium stearate, and 0.6 parts of antioxidant.

[0095] A twin-screw extruder (screw diameter 30mm, aspect ratio 40:1) was used for processing, and the temperature program was: 175℃ for the feeding section, 185℃ for the compression section, 195℃ for the melting section, 205℃ for the homogenizing section, and 195℃ for the metering section. The screw speed was set to 120rpm, the main motor current to 90A, the vacuum degree to -0.08MPa, and the feeding rate to 20kg / h. Kneading blocks were set in the feeding section, melting section, and homogenizing section to improve the mixing and dispersing effect.

[0096] Example 4

[0097] This embodiment provides an environmentally friendly antibacterial PP fan housing material and a preparation method thereof. The method achieves excellent comprehensive performance of the material through the synergistic modification of lignin and montmorillonite. The specific steps are as follows:

[0098] 1. Preparation of modified lignin

[0099] First, the preparation of nano lignin is carried out:

[0100] (1) Take 18 kg of poplar wood kraft lignin with a purity of 99.5%, prepare a sodium hydroxide solution with a concentration of 7 wt% (1.5 parts of sodium hydroxide and 750 parts of deionized water), and stir at 53°C and 600 rpm for 25 minutes. The basic structure of lignin is kept intact by mild alkalization conditions. After vacuum filtration at -0.08 MPa, alkalized lignin is obtained.

[0101] (2) Tetrabutylammonium bromide aqueous solution (0.5 parts of tetrabutylammonium bromide, 800 parts of deionized water, concentration 0.1wt%) was added to the alkalized lignin in sequence, followed by a mixture of 30% hydrogen peroxide and deionized water (mass ratio 35:800), and finally a lignin peroxidase with an activity of 58U / mg (accounting for 0.7wt% of the lignin mass). The reaction was carried out at 53°C and a rotation speed of 635rpm for 1.8h to achieve uniform nano-crystallization of the lignin.

[0102] (3) The reaction solution was filtered, and the precipitate was washed with water three times and anhydrous ethanol (purity 99.8%) twice, dried at 52°C for 2.8 hours, and then crushed at 985 rpm for 9.8 hours at the same temperature to obtain nano-lignin with a particle size of about 280 nm. This condition can obtain a product with a narrow particle size distribution.

[0103] Then carry out thiol modification:

[0104] (4) The nano-lignin was mixed with 1-ethyl-3-methylimidazole hydrogen sulfate with a purity of 99.7% in a mass ratio of 100:28, and put into a reactor. Under the action of a 50 kW power disperser, the mixture was dispersed at 68° C. for 2.5 h to ensure that the lignin was fully dispersed.

[0105] (5) Add 3-mercaptopropionic acid (mass fraction 22 wt%) with a purity of 99.2% to the dispersion, and react at 68°C for 9 h under 0.1 MPa nitrogen protection. Under this condition, a moderate degree of thiolation can be obtained, which is conducive to subsequent modification. After filtration, water washing and drying, thiolated lignin is obtained.

[0106] Finally, carboxyl modification is performed:

[0107] (6) The thiolated lignin, 30% hydrogen peroxide, and sodium periodate were mixed in a weight ratio of 13:7:7, and reacted at 78°C and 68 r / min for 9.5 h. The temperature and time parameters in this step can achieve a higher carboxylation rate. The mixture was filtered, washed with water until neutral, dried at 63°C for 4.8 h, and crushed through a 200-mesh sieve to obtain modified lignin.

[0108] 2. Preparation of Nano-modified Montmorillonite

[0109] (1) Na+ montmorillonite, deionized water, and hexadecyltrimethylammonium bromide were mixed in a mass ratio of 8:4:1 and stirred at 155°C for 11 hours. This condition can ensure that the quaternary ammonium salt is fully intercalated. Centrifuge at 10800 r / min for 17 minutes, wash with deionized water and anhydrous ethanol three times each, and dry at 63°C for 3.8 hours to obtain intercalated modified montmorillonite.

[0110] (2) The intercalated modified montmorillonite was mixed with deionized water in a mass ratio of 8:28, heated to 117°C, and ultrasonically treated for 38 min at a power of 635 W, followed by the addition of a polyethylene glycol solution with a concentration of 23.5% and a molecular weight of 4350. This step optimized the ultrasonic conditions to achieve efficient exfoliation of the montmorillonite.

[0111] (3) The mixture was treated in a six-tube microwave plasma modification device under the conditions of a working power supply of 380 V, a microwave power of 380 W, and an oxygen flow rate of 58 mL / min for 5.5 h to obtain modified montmorillonite with moderate surface polarity.

[0112] 3. Preparation of antibacterial PP fan casing material

[0113] Mix the following components: 88 parts of polypropylene compound (melt index 2.8g / 10min, density 0.915g / cm 3 , homopolymer PP with isotacticity of 97.5% and ethylene content of 4.5wt%, melt index of 4.8g / 10min, density of 0.898g / cm 3 Random copolymer PP is compounded in a mass ratio of 1:1.5), 2.5 parts of polyethylene glycol grafted maleic anhydride (polyethylene glycol molecular weight 3500, maleic anhydride grafting rate 1.1%), 4 parts of modified lignin, 13 parts of nano-modified montmorillonite, 3 parts of silver nitrate, 2.5 parts of coupling agent KH550, 0.4 parts of calcium stearate, and 0.5 parts of antioxidant.

[0114] A twin-screw extruder (screw diameter 30mm, aspect ratio 40:1) was used for processing, and the temperature program was: 172°C for the feeding section, 182°C for the compression section, 192°C for the melting section, 202°C for the homogenizing section, and 192°C for the metering section. The screw speed was set to 115rpm, the main motor current to 88A, the vacuum degree to -0.08MPa, and the feeding rate to 19kg / h. A reverse stirring element was set in the feeding section, and special shear mixing elements were set in the melting section and the homogenizing section to achieve full mixing and dispersion of the components.

[0115] Comparative Example 1 (corresponding to Example 1, verifying the necessity of lignin modification)

[0116] This comparative example uses unmodified lignin, and other components and process parameters are the same as those in Example 1. The details are as follows:

[0117] Commercially available poplar kraft lignin (purity 98%) was used to directly replace the modified lignin, and the proportions of the other components remained unchanged: 80 parts of polypropylene compound, 1 part of polyethylene glycol grafted maleic anhydride, 1 part of unmodified lignin, 8 parts of nano-modified montmorillonite, 1 part of silver nitrate, 1 part of coupling agent KH550, 0.1 part of calcium stearate, and 0.3 part of antioxidant.

[0118] The preparation process is the same as that of Example 1. Since the unmodified lignin lacks active functional groups, its interface bonding with the PP matrix is ​​poor, resulting in a significant decrease in the mechanical properties of the material. At the same time, the unmodified lignin has a strong tendency to agglomerate and poor dispersibility, which affects the uniformity and appearance quality of the material. This fully proves the necessity and innovation of the lignin modification process in the present invention.

[0119] Comparative Example 2 (corresponding to Example 2, verifying the importance of montmorillonite modification)

[0120] This comparative example uses unmodified Na+ montmorillonite to verify the key role of nano-modified montmorillonite. The specific formula is as follows:

[0121] According to the ratio of Example 2, only the nano-modified montmorillonite is replaced with the same amount of Na+ montmorillonite. The Na+ montmorillonite is used directly without intercalation and plasma modification. The results show that due to the small interlayer spacing of Na+ montmorillonite, nano-scale dispersion cannot be achieved, resulting in a significant reduction in the barrier properties of the material and difficulty in controlling the release rate of the antibacterial agent. At the same time, the poor compatibility of the unmodified montmorillonite with the PP matrix results in a significant reduction in the mechanical properties of the material. This illustrates the innovative value of the multi-step modification process of montmorillonite in the present invention.

[0122] Comparative Example 3 (corresponding to Example 3, verifying the synergistic effect of the group distribution ratio)

[0123] This comparative example adjusts the ratio of key components to verify the rationality of the formulation design of the present invention:

[0124] The amount of modified lignin was increased to 8 parts, while the amount of nano-modified montmorillonite was reduced to 5 parts, and the other components and process parameters were the same as those in Example 3. The results showed that excessive modified lignin would lead to a decrease in the processing performance of the material, while less nano-modified montmorillonite could not form an effective barrier network, affecting the durability of the antibacterial performance. This proves the scientific nature of the ratio range of each functional component in the present invention.

[0125] Comparative Example 4 (corresponding to Example 4, verifying the criticality of the preparation process)

[0126] This comparative example changes key process parameters to demonstrate the importance of the process design of the present invention:

[0127] The formulation of Example 4 was adopted, but the following process parameters were changed:

[0128] (1) During the lignin modification process, the thiol reaction temperature was increased to 80 °C and the time was shortened to 4 h;

[0129] (2) When montmorillonite is modified, the intercalation temperature is reduced to 100 °C and the plasma treatment time is reduced to 2 h;

[0130] (3) When preparing the final material, the extrusion temperature was uniformly increased by 20°C.

[0131] The results show that unreasonable process parameters lead to partial degradation of lignin, insufficient modification of montmorillonite, and obvious thermal oxidation of the final material, which verifies the rationality of the process parameter design of the present invention.

[0132] Comparative Example 5 (Verification of the effect of compatibilizer)

[0133] This comparative example removes polyethylene glycol grafted maleic anhydride to verify the necessity of the compatibilizer:

[0134] The formula of Example 1 was adopted, but the polyethylene glycol grafted maleic anhydride was removed, and the amount of PP was increased by 1 part. Other process parameters remained unchanged. The results showed that in the absence of the compatibilizer, the dispersibility of the modified lignin and nano-modified montmorillonite in the PP matrix decreased significantly, and obvious agglomeration occurred, resulting in uneven material properties. This proves the key role of the compatibilizer in the present invention.

[0135] Comparative Example 6 (Verification of the synergistic effect of the antibacterial system)

[0136] This comparative example uses only a single antibacterial component to verify the advantages of multi-component synergistic antibacterial:

[0137] Based on the formula of Example 2, silver nitrate was removed and only the antibacterial effect of modified lignin was relied on. The results showed that a single antibacterial component could not achieve a long-lasting broad-spectrum antibacterial effect, confirming the innovativeness of the synergistic antibacterial system formed by the antibacterial agent, modified lignin, and nano-modified montmorillonite in the present invention.

[0138] Based on the mechanism of action of the present invention, the following performance test scheme is designed:

[0139] 1. Test methods and conditions

[0140] 1. Mechanical properties test

[0141] Tensile performance test according to GB / T1040.2-2006 standard:

[0142] The CMT4204 universal testing machine was used, with a test speed of 50 mm / min, a temperature of 23 ± 2 °C, and a relative humidity of 50 ± 5%. The specimen was dumbbell-shaped with a gauge length of 50 mm. Five parallel samples were tested in each group and the average value was taken.

[0143] 2. Antibacterial performance test

[0144] Antimicrobial activity test according to GB / T31402-2015:

[0145] Escherichia coli (ATCC25922) and Staphylococcus aureus (ATCC6538) were selected as indicator bacteria. The culture conditions were 37°C, 24 hours. The plate counting method was used to determine the number of colonies. The antibacterial rate calculation formula is:

[0146] Antibacterial rate (%) = (number of colonies in the control group - number of colonies in the experimental group) / number of colonies in the control group × 100%

[0147] 3. Nanodispersion Characterization

[0148] Observation by transmission electron microscopy (TEM):

[0149] A FEITecnai G2F20 transmission electron microscope was used with an accelerating voltage of 200 kV. The samples were observed after being sliced ​​into ultrathin sections (thickness of about 100 nm).

[0150] 4. Crystallization performance analysis

[0151] Using Differential Scanning Calorimetry (DSC):

[0152] A TAQ2000 DSC instrument was used with a heating rate of 10°C / min, a temperature range of 25-200°C, and a nitrogen atmosphere.

[0153] 5. Thermal stability test

[0154] Using Thermogravimetric Analysis (TGA):

[0155] A TAQ500 thermogravimetric analyzer was used with a heating rate of 20°C / min, a temperature range of 25-600°C, and a nitrogen atmosphere.

[0156] 6. Water vapor transmission rate test

[0157] Tested according to GB / T1037-1988:

[0158] A W3 / 030 water vapor transmission rate tester was used, with the test temperature at 38±0.2°C and relative humidity at 90±2%.

[0159] The test results are as follows:

[0160] Table 1 Mechanical properties test results

[0161]

[0162]

[0163] Table 2 Antibacterial performance test results

[0164]

[0165] Table 3 Thermal stability and barrier performance test results

[0166]

[0167] Table 4 Crystallization performance test results

[0168]

[0169]

[0170] Table 5 Nanodispersion characterization results

[0171] Sample No. Average particle size of lignin (nm) Montmorillonite interlayer spacing (nm) Dispersion Index Agglomeration degree (%) Example 1 285 3.8 1.15 4.2 Example 2 262 4.2 1.12 3.8 Example 3 245 4.5 1.08 3.2 Example 4 258 4.3 1.1 3.5 Comparative Example 1 685 2.2 1.85 12.5 Comparative Example 2 542 2.5 1.65 10.8 Comparative Example 3 485 2.8 1.52 9.2 Comparative Example 4 625 2.3 1.78 11.5 Comparative Example 5 720 2.1 1.92 13.2 Comparative Example 6 508 2.6 1.58 9.8

[0172] Based on the above comprehensive test data, the present invention shows many technical breakthroughs and excellent performance. First, in terms of the microstructure of the material, transmission electron microscopy observations show that the multi-step modified lignin presents a uniform nano-scale dispersion state, and its average particle size can be controlled within the range of 245-285nm, which is much better than the unmodified control group. More importantly, the thiol and carboxyl groups introduced on the surface of the modified lignin have a strong interaction with the PP molecular chain, which not only provides physical entanglement points, but also significantly enhances the interfacial bonding strength through chemical bonding.

[0173] Secondly, in terms of the modification effect of montmorillonite, the innovative three-step modification process adopted by the present invention significantly increases the interlayer spacing of montmorillonite from the original 1.2nm to 3.8-4.5nm. This substantial increase in interlayer spacing creates favorable conditions for the intercalation of PP molecular chains. Furthermore, the polar group network constructed on the surface of montmorillonite by plasma treatment forms a synergistic effect with the modified lignin, jointly improving the comprehensive performance of the composite material.

[0174] In terms of crystallization behavior, the material system of the present invention exhibits a unique induced crystallization effect. The crystallinity of the example group is generally 8-10 percentage points higher than that of the control group, and the crystallization half time is shortened by about 40%, which indicates that the modified nanofiller has a significant nucleation effect. In particular, in Example 3, the crystallinity reaches 49.8%, and the crystallization half time is only 3.5 minutes. This rapid crystallization behavior is of great significance to improving the production efficiency of the material.

[0175] The most outstanding is the innovative breakthrough of the present invention in terms of performance synergy. Taking Example 3 as an example, its tensile strength is increased by 37% compared with that of Comparative Example 1, while the elongation at break is still maintained at a high level of 165%. This significant improvement in mechanical properties stems from the unique network structure formed by modified lignin and nano-montmorillonite in the PP matrix. The thiol groups on the surface of lignin are physically entangled with the PP molecular chains through free radical transfer, while the carboxyl groups strongly interact with the polar groups on the surface of montmorillonite, jointly constructing an efficient stress transfer network.

[0176] In terms of antibacterial properties, the present invention achieves a perfect unity of long-lasting antibacterial and sustained-release regulation. The embodiment group still maintains an antibacterial efficiency of more than 95% after 7 days, far exceeding the 75-85% of the control group. This long-lasting antibacterial effect is attributed to the maze structure constructed by nano-modified montmorillonite, which not only controls the release rate of silver ions, but also forms a stable network of antibacterial active sites through synergistic effects with modified lignin. At the same time, the antioxidant properties of modified lignin effectively prevent the oxidative inactivation of silver nanoparticles, further extending the antibacterial duration of the material.

[0177] The synergistic effect of the present invention was further confirmed by the thermal stability test. The initial degradation temperature of the example group was significantly higher than that of the control group by 20-35°C. This improvement in thermal stability is due to multiple protection mechanisms: thiolated lignin inhibits thermal oxidative degradation by free radical capture, and nano-montmorillonite delays oxygen diffusion by building a barrier network. The synergistic effect of the two components significantly improves the heat resistance of the material.

[0178] The above description is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.

Claims

1. An antibacterial PP fan shell material, characterized in that: By weight, it is composed of the following components: 80-90 parts of polypropylene compound, 1-3 parts of polyethylene glycol grafted maleic anhydride, 1-5 parts of modified lignin, 8-15 parts of nano-modified montmorillonite, 1-4 parts of silver nitrate, 1-3 parts of coupling agent KH550, 0.1-0.5 parts of calcium stearate, and 0.3-0.6 parts of antioxidant; Wherein, the polypropylene compound is prepared by mixing homopolymer PP and random copolymer PP in a mass ratio of 1:1.5; The homopolymer PP has a melt index of 2.0-3.0 g / 10 min at 230°C / 2.16 kg and a density of 0.90-0.92 g / cm 3 , isotacticity is 96-98%; The random copolymer PP has an ethylene content of 3-5wt%, a melt index of 230°C / 2.16k of 4.0-5.0g / 10min, and a density of 0.89-0.90g / cm 3 .

2. The antibacterial PP fan housing material according to claim 1, characterized in that: The polyethylene glycol grafted maleic anhydride has a molecular weight of 2000-4000, a maleic anhydride grafting rate of 0.8-1.2%, and a melt index of 190° C. / 2.16 kg of 5-8 g / 10 min.

3. The antibacterial PP fan housing material according to claim 1, characterized in that: The antioxidant is a mixture of type 1010 antioxidant and type 168 antioxidant in a mass ratio of 1:

1.

4. The antibacterial PP fan housing material according to claim 1, characterized in that: The modified lignin is prepared by the following steps: (1) adding nano-lignin and 1-ethyl-3-methylimidazolium hydrogen sulfate in a mass ratio of 100:20-30 into a reaction kettle, and dispersing them at a temperature of 65±4° C. for 1-3 hours under the action of a disperser with a power of 30-60 kW to obtain a dispersion; (2) adding 15-25 wt% of 3-mercaptopropionic acid to the dispersion in step (1), reacting at 65±4° C. for 6-10 h under 0.1 MPa nitrogen protection, and filtering, washing with water, and drying to obtain thiolated lignin; (3) The thiolated lignin described in step (2), 30% hydrogen peroxide, and sodium periodate are mixed in a weight ratio of 10-15:5-8:5-8, reacted at a temperature of 70±10° C. and a rotation speed of 60±10 r / min for 8±2 h, filtered, washed with water until neutral, dried at 60±5° C. for 4±1 h, and crushed through a 200-mesh sieve to obtain the modified lignin.

5. The antibacterial PP fan housing material according to claim 4, characterized in that: The nano lignin is prepared by the following steps: (1) stirring poplar wood kraft lignin and a sodium hydroxide solution with a mass concentration of 5-10 wt% at 52±3°C and a rotation speed of 400±200 rpm for 30±10 min, and filtering to obtain alkalized lignin; (2) adding a tetrabutylammonium bromide solution having a concentration of 0.0875±0.0375wt%, a mixed solution of 30% hydrogen peroxide and deionized water in a mass ratio of 32.5±7.5:750±250, and 0.5-1.0wt% lignin peroxidase to the alkalized lignin in step (1), and reacting at 52±3°C and a rotation speed of 600±50rpm for 1.5±0.5h; (3) The reaction solution of step (2) was filtered, and the precipitate was washed with clean water 3 times and anhydrous ethanol 2 times, dried at 50±5° C. for 2±1 h, and then crushed at 50±5° C. and 950±50 rpm for 9±1 h to obtain the nano-lignin.

6. The antibacterial PP fan housing material according to claim 1, characterized in that: The nano-modified montmorillonite is prepared by the following steps: (1) Na+ montmorillonite, deionized water, and hexadecyltrimethylammonium bromide were mixed in a mass ratio of 1-10:1-5:1, stirred at 140±20°C for 9±3h, centrifuged at 10500±500r / min for 15±5min, washed with deionized water 3 times, washed with anhydrous ethanol 3 times, and dried at 60±5°C for 3±1h to obtain intercalated modified montmorillonite; (2) mixing the intercalated modified montmorillonite described in step (1) with deionized water in a mass ratio of 1-10:20±10, heating to 115±5° C., ultrasonically treating for 30±10 min, and adding a polyethylene glycol solution with a concentration of 22.5±2.5% and a molecular weight of 4000±500; (3) treating the mixture obtained in step (2) in a six-tube microwave plasma modification device under the conditions of a working power supply of 300±100V, a microwave power of 300±100W, and an oxygen flow rate of 50±10mL / min for 4.5±1.5h to obtain the nano-modified montmorillonite.

7. A method for preparing the antibacterial PP fan casing material according to any one of claims 1 to 6, characterized in that: The following steps are involved: The components are put into a twin-screw extruder and extruded into granules, wherein: The screw diameter is 30 mm and the aspect ratio is 40:1; The temperature of the feeding section is 165±5℃, the temperature of the compression section is 175±5℃, the temperature of the melting section is 185±5℃, the temperature of the homogenization section is 195±5℃, and the temperature of the metering section is 185±5℃; The screw speed is 100±20rpm, the main motor current is 80±10A, the vacuum degree is -0.08MPa, and the feeding rate is 15±5kg / h.

8. The preparation method according to claim 7, characterized in that: The order of adding the components is: first adding the polypropylene compound and polyethylene glycol grafted maleic anhydride, and then adding the modified lignin, nano-modified montmorillonite, silver nitrate, coupling agent KH550, calcium stearate and antioxidant in sequence.

9. The preparation method according to claim 7, characterized in that: The screw assembly of the twin-screw extruder consists of a feeding section, a compression section, a melting section, a homogenizing section and a metering section, and the screw elements are arranged in sequence along the length direction of the barrel.

10. The preparation method according to claim 7, characterized in that: A reverse stirring element is arranged in the feeding section, and kneading blocks are arranged in the melting section and the homogenizing section respectively.

Citation Information

Cited By

  • Hemp tree powder bio-based degradable material and preparation method thereof

    CN120829627A

  • Antiviral functional decorative material

    CN121319526A

  • Antiviral functional decorative material

    CN121319526B